Enriching Psychological Assessment Using a Person-Specific Analysis of Interpersonal Processes in Daily Life - Roche, M.; Pincus, A.; Rebar, Amanda; Conroy, D.; Ram, N. (SAGE Publications, 2014)
© The Author(s) 2014. We present a series of methods and approaches for clinicians interested in tracking their individual patients over time and in the natural settings of their daily lives. The application of person-specific analyses to intensive repeated measurement data can assess some aspects of persons that are distinct from the valuable results obtained from single-occasion assessments. Guided by interpersonal theory, we assess a psychotherapy patient’s interpersonal processes as they unfold in his daily life. We highlight specific contexts that change these processes, use an informant report to examine discrepancies in his reported interpersonal processes, and examine how his interpersonal processes differ as a function of varying levels of self-esteem and anger. We advocate for this approach to complement existing psychological assessments and provide a scoring program to facilitate initial implementation.